Equity and Homelessness. Issue 1 (February 2020) - Yu, Andy
Abstract : I argue that homelessness calls for equitable intervention. The motivation for such intervention involves the state's provision of the system of property rights. This will be one that is responsible for but can also solve homelessness. The nature of the equitable interest responds to this motivation. There is a negative equitable right for the state not to exercise its right to exclude people from state-owned property against homeless people. There is also a positive equitable right for the state to provide housing to the homeless, or at least take steps towards doing so.